Ensino médio integrado, a nossa escola do trabalho: repensando a formação dos jovens brasileiros a partir dos fundamentos da pedagogia soviética e as interfaces curriculares das ciências da natureza - Silva, Ariana Cárita de Assis Marinho (2023)
Education has always been and will remain invariably associated with the ongoing corporate project. Human formation is part of a whole called society and not a cool entity with unrestricted transformative potential. The change of concrete conditions goes through the transformation of this whole, also modifying the educational processes. In Brazilian class society, sustained by dependent capitalism, working-class education has historically constituted a dual system, where knowledge and advancement in studies are restricted to those belonging to the dominant class, leaving young people from the exploited classes with access to training for alienated work. Even in this context dominated by power relations, emancipatory educational tactics emanate from the contradictory dynamics of the capitalist world, among them Integrated Secondary Education (EMI), a curricular model present in the Federal Institutes of Education, Science and Technology. However, in the face of attacks and counter-reforms in education intensified after the 2016 Coup, the EMI demands means for its resistance and objectification. And for the purpose of this strengthening, through a bibliographical study, we seek in the Soviet Work School, a proposal based on Marxian polytechnics, principles and potential foundations for the resistance process of the EMI in Brazil. We are guided, therefore, by the following question: What principles and foundations of Soviet Pedagogy (PS), idealized in the period from 1917 to 1930, can be rescued as references for the strengthening of the Integrated Curriculum in the EMI, historical and contradictory form in the name of the dispute for a Polytechnic Human Formation in Brazil? In the perspective of answering this question, this research was based and organized by the general objective of making a study of the movement from the Curriculum with a centrality in the Natural Sciences (singular) to Human Formation (universal) with the mediation (particular) of PS and the EMI. After a historically referenced analysis, the topicality of PS proved to be a central element in this process of objectifying the integrated curriculum in Brazil, enhancing both curricular integration and aspects of polytechnics in EMI, overcoming the disciplinary and fragmented nature of training with end in itself or training for alienated work. Finally, we understand that in the war for the education of the working class, the strategy of integral, omnilateral or polytechnic human formation relies on the expressive tactics of the Soviet Work School, which we have appropriated for the strengthening of our Work School.